18 tiny deaths ebook The untold story of frances glessner lee and the invention of modern forensics. - Goldfarb, Bruce (2020)
A captivating blend of history, women in science, and true crime, 18 Tiny Deaths tells the story of how one woman changed the face of forensics forever. Frances Glessner Lee, born a socialite to a wealthy and influential Chicago family in the 1870s, was never meant to have a career, let alone one steeped in death and depravity. Yet she developed a fascination with the investigation of violent crimes, and made it her life's work. Best known for creating the Nutshell Studies of Unexplained Death, a series of dollhouses that appear charming—until you notice the macabre little details: an overturned chair, or a blood-spattered comforter. And then, of course, there are the bodies—splayed out on the floor, draped over chairs—clothed in garments that Lee lovingly knit with sewing pins. 18 Tiny Deaths, by official biographer Bruce Goldfarb, delves into Lee's journey from grandmother without a college degree to leading the scientific investigation of unexpected death out of the dark confines of centuries-old techniques and into the light of the modern day. Lee developed a system that used the Nutshells dioramas to train law enforcement officers to investigate violent crimes, and her methods are still used today. The story of a woman whose ambition and accomplishments far exceeded the expectations of her time, 18 Tiny Deaths follows the transformation of a young, wealthy socialite into the mother of modern forensics... "Eye-opening biography of Frances Glessner Lee, who brought American medical forensics into the scientific age...genuinely compelling." —Kirkus Reviews "A captivating portrait of a feminist hero and forensic pioneer." —Booklist